2021
DOI: 10.1038/s41380-021-01309-5
|View full text |Cite
|
Sign up to set email alerts
|

The acid sphingomyelinase/ceramide system in COVID-19

Abstract: Acid sphingomyelinase (ASM) cleaves sphingomyelin into the highly lipophilic ceramide, which forms large gel-like rafts/platforms in the plasma membrane. We showed that SARS-CoV-2 uses these platforms for cell entry. Lowering the amount of ceramide or ceramide blockade due to inhibitors of ASM, genetic downregulation of ASM, anti-ceramide antibodies or degradation by neutral ceramidase protected against infection with SARS-CoV-2. The addition of ceramide restored infection with SARS-CoV-2. Many clinically appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 130 publications
4
127
0
Order By: Relevance
“…First, antidepressants have been shown to interact with the sphingomyelinase/ceramide system, which is likely required to facilitate angiotensin-converting enzyme 2 (ACE2) binding of the SARS-CoV-2 and thereby impair viral host cell entry. [10][11][12] In addition to antidepressant drugs, several medications share the property of functional inhibition of the acid sphingomyelinase. Recent observational data show a reduced likelihood of intubation or death in (n = 2846) COVID-19-infected patients who are treated with any of the functional sphingomyelinase/ceramide system inhibitory drugs.…”
Section: Potential Explanation For These Findingsmentioning
confidence: 99%
“…First, antidepressants have been shown to interact with the sphingomyelinase/ceramide system, which is likely required to facilitate angiotensin-converting enzyme 2 (ACE2) binding of the SARS-CoV-2 and thereby impair viral host cell entry. [10][11][12] In addition to antidepressant drugs, several medications share the property of functional inhibition of the acid sphingomyelinase. Recent observational data show a reduced likelihood of intubation or death in (n = 2846) COVID-19-infected patients who are treated with any of the functional sphingomyelinase/ceramide system inhibitory drugs.…”
Section: Potential Explanation For These Findingsmentioning
confidence: 99%
“…To contain the current pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a better understanding of the underlying mechanisms and the high interindividual differences in susceptibility is essential. A number of recent studies point to changes in the sphingolipid metabolism (Kornhuber et al 2021). Sphingolipids such as sphingomyelin (SM) and ceramide (Cer) not only serve as physical membrane components and as ligands on their own, but they also influence the local composition and fluidity of the plasma membrane and thereby the localization and activity of proteins involved in receptor-mediated signaling (Hannun and Obeid 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs were therefore named functional inhibitors of ASM (FIASMA, (Kornhuber et al 2010)) and include commonly used antidepressants like fluoxetine, amitriptyline and fluvoxamine. Interestingly, an antiviral effect of FIASMAs against SARS-CoV, Middle East Respiratory Syndrome (MERS)-CoV and also especially SARS-CoV-2 has been demonstrated by various approaches in silico, in vitro and in vivo as summarized in recent reviews (Kornhuber et al 2021;Le Corre and Loas 2021) (Loas and Le Corre 2021). SARS-CoV-2 is thought to activate the ASM/Cer system, resulting in the formation of Cer-enriched membrane domains (Carpinteiro et al 2020) (Schneider-Schaulies et al 2021) and clustering of angiotensin-converting enzyme 2 (ACE2), the cellular receptor of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been found that the COVID-19 virus activates the ceramide system that then facilitates viral entry into cells [ 27 ]. The sphingomyelin/ceramide system can be altered by SSRIs so that ceramide levels are reduced and this may prevent COVID-19 replication [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%